2015
DOI: 10.1111/pere.12082
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from conflict and revival of intimacy in cohabiting couples

Abstract: Couples who seek a stable and satisfying relationship must recover emotionally and reestablish their intimate connection after their conflicts are over. In a 3-week diary study, 100 cohabiting couples reported on their daily moods, intimacy, relationship satisfaction, and conflicts. Results indicated that on days following a conflict, couple partners have worse mood, less satisfaction, and less self-disclosure than on other days. Attachment security and intimacy partially moderated the ability of relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 39 publications
5
57
2
Order By: Relevance
“…Consistent with prior evidence of links between attachment and conflict recovery (Prager et al, 2015; Salvatore et al, 2011), recovery sabotage was strongly associated with lower actor parental attachment avoidance and higher parental attachment anxiety. For highly anxious people, effective recovery appears to be rather difficult, perhaps reflecting the regulatory challenges associated with trying to contain emotional and behavioral responses to a potential relationship threat such as conflict (Feeney, 2004).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Consistent with prior evidence of links between attachment and conflict recovery (Prager et al, 2015; Salvatore et al, 2011), recovery sabotage was strongly associated with lower actor parental attachment avoidance and higher parental attachment anxiety. For highly anxious people, effective recovery appears to be rather difficult, perhaps reflecting the regulatory challenges associated with trying to contain emotional and behavioral responses to a potential relationship threat such as conflict (Feeney, 2004).…”
Section: Discussionsupporting
confidence: 83%
“…Nonetheless, this study extends prior evidence of links between infant attachment to caregivers and later recovery behavior in adult romantic relationships (Salvatore et al, 2011) and between adult self-reported attachment to romantic partners and the psychological experience of recovery (Prager et al, 2015). Links between attachment and conflict recovery have now been observed in three distinct samples, in different assessment periods (infant vs. adult attachment), using different measurement strategies (the Strange Situation Procedure vs. self-reported attachment style), and different attachment figures (parents vs. the current romantic partner).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations